Synthesis, antifungal, antitumor and antiinflammatory activities of some new 5-substitutedarylimino-2-N-p-tolylsulphonyl-3-oxo-1,2,4-thiadiazolidines - Manna P.; Singh R.; Narang K.K.; Manna S.K. (My University, 2025)
Synthesis of 5-arylimino-2-N-p-tolylsulphonyl-3-oxo-1,2,4-thiadiazolidines (IV) have been achieved by oxidative debenzylation and cyclization with molecular bromine in moistened chloroform from the corresponding 1-aryl-5-p-tolylsulphonyl-2-S-benzyliso-4-biurets (III) in moderate yield. Biurets in turn were prepared by the condensation of 1-aryl-2-S- benzylisocarbamides with p-tolylsulphonylisocyanate. These thiadiazodines (IV) were characterized by elemental analyses, 1H NMR, 13C-NMR, IR spectra and mass spectral data. Antifungal screenings of title compounds against ten fungi have been achieved by glass slides methods and their comparative findings have been critically examined and reported. The compound possessing a chloro group at p-position has shown maximum inhibition (98.8%) against Aspergilum flavus at 1000 μg/ml concentration. The compound possessing a chloro group at p-position and the other possessing a methyl group at p-position have shown potent antiinflammatory and antitumor properties.